Anaerobic treatment of spentwash for recovery of clean energy. (2020) - Mohan, Chander; Bashir, Misbah; Annachhatre, Ajit P.
Abstract: A laboratory scale anaerobic Continuous Stirrer Tank Reactor (CSTR) was established to treat synthetic wastewater simulating diluted spentwash from molasses-based distillery. A CSTR of effective volume 4.75 L was seeded by the seed sludge obtained from Sewage Treatment Plant (STP) and slurry from the biogas plant, both situated at IIT Mandi. The reactor was in operation for 151 days with the influent COD (amount of equivalent oxygen required to oxidise organic as well as inorganic matter completely) of 6000–8000 mg/l and loading rate of 0.15–0.61 g COD/L.d. The reactor was operated in the temperature range of 30–38 °C and pH of influent was maintained in the range 6.5–8.0. Results obtained from the study indicates that COD removal efficiency about 85% with methane production of 0.60 L/d. Methane content in the biogas was around 68%, which indicates high quality biogas production and the methane yield of 0.2932 L/(g COD removed). In parallel with the CSTR, an Upflow Anaerobic Sludge Blanket (UASB) reactor with effective volume 7.1 L was also established. The preliminary results during the start-up phase of 60 days of the UASB reactor indicated the maximum COD removal efficiency of 66% and the biogas production of 0.34 L/d.